Islamic Renewal Project: Ḥassan Ḥanafī and Indonesian Intellectual Muslims - Syafieh Syafieh (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
This article aims to examine the Islamic reform project through the reconstruction of theology and thought carried out by Ḥassan Ḥanafī and Indonesian Muslim intellectuals. Ḥassan Ḥanafī considered the need to reconstruct classical theology, which is regarded as too abstract in describing theological terms and does not have a strong practical basis as a value for the action. In criticizing classical theology, Ḥassan Ḥanafī offers two theocentric theories, namely language analysis, and social reality analysis. Conducting library research that relies on written materials and analyzed with content analysis techniques, the present study shows that Ḥassan Ḥanafī’s theoanthropocentric theological ideas have intersections with the development of Islamic thought in Indonesia. This can be proven by the translation of Ḥassan Ḥanafī’s books and examining his thoughts in Indonesia. Apart from that, Ḥassan Ḥanafī’s thoughts find relevance in Indonesia because Indonesian Muslim scholars carry out similar reform projects.